Microsatellite loci in the oceanic whitetip shark and cross-species amplification using pyrosequencing technology - Mendes, N. J. [UNESP]; Cruz, V. P. [UNESP]; Mendonça, Fernando Fernandes [UNESP]; Pardo, B. G.; Coelho, R.; Ashikaga, F. Y. [UNESP]; Camargo, S. M. [UNESP]; Martinez, P.; Oliveira, C. [UNESP]; Santos, M. N.; Foresti, F. [UNESP] (Springer, 2015)
Among the pelagic shark species most impacted by fisheries, the oceanic whitetip shark (Carcharhinus longimanus) has shown signs of population declines. In this study, we developed 12 microsatellite markers using next generation sequencing (454 pyrosequencing) in C. longimanus for further use in population screening. The genetic diversity of these loci was assessed in 28 individuals and a total of 35 alleles were identified, ranging from four to eight alleles per locus (5.9 alleles on average). Cross-species amplification of these markers was successful in five loci for C. acronotus, C. perezi and Galeocerdo cuvier. The developed microsatellite markers will be useful in analyzing the population genetics structure of the oceanic whitetip shark and other Carcharhinidae species.
Keywords: Conservation; Population genetics; Next generation sequencing; Carcharhinus